Mercantilização do ensino superior e cursos ilegais em Serviço Social: a particularidade dos cursos livres e/ou de extensão - Oliveira, Nísia Luiza de Andrade (2022)
The present research has as its object of study the discussion of the commodification of Graduate Education, its relation to Distance Education (DL) and the formation of an irregular undergraduate market. The work is methodologically based on the historicaldialectical materialism method. Its general objective is to analyze the expansion and irregular offering of extension and/or free courses and its implications on Social Work undergraduate courses in the Northeast region. As specific objectives were approached the process of commodification of Graduate Education in Brazil and its particularity in professional training in Social Work; characterization and analysis of extension and/or free courses offered in Social Work in the Northeast region; apprehension and evaluation of the position of the CFESS-CRESS set and the actions and strategies developed against the illegal offer of extension and/or free courses. It's about a documentary research based on the orientation of the Federal Council of Social Work (CFESS) "Extension and/or free courses illegally offered as undergraduate courses in Social Work"; as well as in reports about irregular courses, legal process, and the opinion of the Ministry of Education (MEC). Initially, the work carried out a bibliographical survey about the structural crisis from 1970 on, the productive restructuring, flexible accumulation, and its implications for social policies. Next, discussed education in the capitalist sociability and the placement of this right as merchandise, as well as a mechanism to train the labor force for the system itself. As far as the Brazilian reality is concerned, the expansion of Graduate Education from Fernando Henrique Cardoso's government (1995-2002) to Jair Messias Bolsonaro's (2019-), especially focused on the private sector and the expansion of vacancies through DL. It also analyzed the impact of this market perspective on Social Work, professional training, and the precariousness of teaching. From the study it was possible to conclude that there is a maneuver to offer extension and/or free courses in an illegal way that reaches other areas of knowledge such as Pedagogy. It was identified the majority presence of irregular Social Work courses in the Northeast region. It was noticed yet the formation of an educational market geared towards fake degrees and the ease of its execution through DL. Finally, it was identified the relevant articulation and development of campaigns by the CFESS-CRESS set to raise awareness about the offer of extension and/or free courses in Social Work with the purpose of orienting professionals, students, and society about their existence, as well as the imposition of one more challenge to the profession through the commercialization of education that favors the precariousness of training.